COMMUNITY BEHAVIOR IN ENVIRONMENTAL PRESERVATION EFFORTS (Case Study of the Wai Lawe Spring in the Kumah Protected Forest, East Adonara District, East Flores Regency) - Peran, Anselaus Pehan; Kaho, Ludji Michael Riwu; Pramatana, Fadlan; Mau, Astin Elise (Media Konservasi, 2023)
Wai Lawe Spring is the primary water source in Puhu and Tapobali Village. This spring is located in the Kumah protected forest area, with an area of 141.41 ha. Still, in its management, it was found that community activities threatened the preservation of the spring, namely land clearing activities in the spring area, which caused a decrease in the discharge of the Wai Lawe spring. The research aims to analyze the behavior of Puhu and Tapobali Village in utilizing and maintaining the sustainability of the Wai Lawe spring in the Kumah protected forest, East Adonara District, East Flores Regency. Data was collected using observation, interviews, and documentation and then analyzed descriptively and qualitatively. The research shows Puhu and Tapobali villagers' behavior in utilizing and maintaining the sustainability of the Wai Lawe spring can be seen from the conservation actions, which they believe that by planting and caring for plants, they have participated in maintaining the sustainability of the spring. Conservation actions are also shown by distributing water to the community fairly. Although there are still people who clear land for shifting cultivation, the villages of Puhu and Tapobali still have traditional cultures that strongly support spring conservation activities. People who obey the rules prefer to use the tumpeng sari farming system without changing the function of the forest. Key words: community behavior, East Adonara, East Nusa Tenggara, protected forest, spring